Paediatric sedation with intranasal dexmedetomidine: Protocol for a systematic review and meta-analysis - Katrine Dueholm Nissen; Caroline Margaret Moos; Andras Wolf; Thomas Strøm (PLoS ONE, 2025)
Introduction Sedation ensures a child remains motionless during a procedure and decreases anxiety. Several pharmacologic regimes exist for paediatric sedation. However, often, intravenous cannulation is required, causing distress for the child. Creating a low-stress environment for children during medical procedures is crucial. Intranasal dexmedetomidine offers a promising alternative by either removing the need for intravenous cannulation or significantly reducing stress and anxiety when cannulation is necessary. We aim to investigate the safety and efficiency of sedating children with intranasal dexmedetomidine. Methods and analysis We will systematically search MEDLINE (Ovid), Embase (Ovid), CINAHL (EBSCO), CENTRAL, Clinicaltrials.gov, and the WHO ICTRP portal. We will include all randomized controlled trials (RCT) that investigate the use of intranasal dexmedetomidine compared to alternative sedatives for premedication or sedation of children. Two researchers will independently screen title/abstract and full-text articles for eligibility using Covidence. Our primary outcome is sedation success rate. RCTs that meet the inclusion criteria will form the unit of analysis. Data extracted from each study will be presented in table format (S2 Table). Information on parameters that describe safety and efficiency outcomes will be extracted and analysed. Outcome data will be reported as risk ratios and 95% confidence intervals (CI) for dichotomous outcomes or mean and standardized mean differences with 95% CI for continuous outcomes. The assessment of statistical heterogeneity will be examined using Chi2- and I2-statistics. PROSPERO registration number CRD42024532993 Discussion Sedation with intranasal dexmedetomidine is not common practice in all countries, though the medicament has the potential to provide a child-friendly approach to sedation and premedication. Reviews on the area are conflicting, and new RCT studies have been published. Our systematic review aims to comprehensively assess intranasal paediatric sedation, focusing on dexmedetomidine and guiding clinicians in daily decision-making for optimal paediatric sedation.